Perbandingan Sistem Hukum Perdata Negara Inggris (Common Law System) Dan Negara Indonesia (Civil Law Sytem) - Betaubun, Restu Monika Nia; Ngilawane, Cavin George (Universitas Musamus, 2024)
Comparative law in its content clearly requires a comparison of two or more legal systems, two or more legal traditions. In this world we do not find only one legal system, but more than one legal system, namely the Civil Law System and the Common Law System. Furthermore, in this article what will be studied is the comparison of the civil law system of the English Common Law System and the Indonesian Civil Law System. The formulation of the problem in this article is how the civil law system differs between the English Common Law and the Indonesian Civil Law in terms of the structure of the judicial body, the source of procedural law, the judicial process, the presence or absence of a jury system, and the position of judges and lawyers in the judicial process. The legal research method used is normative legal research method. The results obtained are 1) In England civil cases are generally tried in the Country Court for simple cases and the High Court of Justice for complex cases. Appeals are filed at the Court of Appeal while cassations at the UK Supreme Court. In Indonesia, criminal and civil cases are tried in the District Court, appeals to the High Court and cassations to the Supreme Court. 2) The sources of English law are jurisprudence, statute law, custom, and reason. Indonesian sources of law are legislation, custom, treaties, jurisprudence, and doctrine. 3) In both the UK and Indonesia the first trial is an peaceful attempt, the difference is that in the UK it is presided over by a former barrister or solicitor while in Indonesia it is presided over by a judge. 4) The UK generally does not recognize the jury system, except in complex criminal and civil cases, while Indonesia does not recognize the jury system. 5) In England the judge plays an active role in the trial, while in Indonesia the judge is passive. 6) In England lawyers are divided into two, namely solicitors and barristers, while Indonesia does not recognize two divisions of lawyers. Keywords: comparative law sytem, common law, civil law